Application Of Interpersonal Communication As Behavioral Strategies Of Victims Of Bullying In PAUD - Fadhilah Syam Nasution; Nanda Ayu Setiawati; Rosina Zahra; Edy Surya (CV. Pusdikra Mitra Jaya, 2022)
Interpersonal communication or interpersonal communication is the process of exchanging information between one person and another, usually between two people. In interpersonal communication itself there are many factors that improve interpersonal relationships, for example from the quality of communication itself. Communication patterns are not ideal can arise when someone gets bad treatment. The problem formulation of this research is how to apply interpersonal communication as a behavior strategy for bullying victims in PAUD?. The purpose of this study was to apply interpersonal communication as a behavioral strategy for victims of bullying in PAUD. This research approach is a qualitative research. Qualitative research method is a research method based on the philosophy of postpositivism, used to examine the condition of natural objects, data collection techniques are carried out by triangulation (combined). The results of this study indicate that bullying behavior in students that occurs in schools is low. This is different from the initial research data which shows that bullying behavior in students is high. The discussion of this research is that interpersonal communication is correlated with bullying behavior and has a greater correlation and contribution to bullying behavior.